ANALISIS SISTEM PENGENDALIAN PERSEDIAAN BARANG DAGANG PADA PD. ASIA AGUNG PONTIANAK - Debora, Memes; Febriati; Kristiawati, Endang (Jurnal Akuntansi, Auditing dan Investasi, 2023)
Inventory of trade goods is trade goods owned by the company for sale or reprocessing Inventory of trade goodsplays an important role in the process of running a company. This study aims to determine the control of tradegoods inventory at PD. Asia Agung Pontianak. By using the type of research descriptive qualitative method anddata analysis techniques used are conducting surveys, interviews, Flowchart system analysis analyzing anddrawing conclusions from the results of the answers to the Internal Control Questionnaire. Based on the resultsof this study, it shows that, in controlling the inventory of trade goods, there are still several weaknesses, namelywhere there are still duplicate tasks in the warehouse section with planning the procurement of goods and it isalso known that there is an untimely delivery of goods to retailers which is an obstacle in controlling the inventoryof trade goods and no sanctions are given to employees who commit a negligence. So that improvements andimprovements need to be made in every control of trade goods inventory to obtain more optimal results.